Flourish-HE: An online positive education programme to promote university student wellbeing - Morgan, Blaire; Simmons, Laura; Ayles, Nikki (Frontiers in Education, 2023)
Student mental health and wellbeing is both a priority and area of challenge within Higher Education, with providers seeing an increased demand for mental health, counselling and wellbeing support. The current paper argues that an effective preventative approach to supporting university student wellbeing is one that: (a) addresses student wellbeing using a holistic approach; (b) is underpinned by a comprehensive wellbeing theory; (c) aims to promote key dimensions of individual and collective wellbeing; and (d), can align with HE structures and strategies. Consequently, we describe and evaluate a multi-faceted eight-week online wellbeing programme – Flourish-HE – which follows a positive education ethos and is underpinned by the PERMA-H theory of wellbeing. The mixed method evaluation of Flourish-HE employs an explanatory sequential design with matched pre-post quantitative surveys (N = 33) and follow up qualitative interviews (N = 9). The surveys examine pre-post changes in PERMA-H wellbeing facets, mental health outcomes and sense of community with quantitative results indicating significant increases in positive emotion, positive relationships, meaning or purpose in life, overall mental wellbeing and sense of (course) community following participation in the programme, alongside decreases in depressive symptomology. The qualitative findings supported, and provided further explanation for, the pre-post-test differences and highlighted several barriers to engagement in the programme (e.g., unfavourable preconceptions) and future considerations (such as supporting longer-term effects). The evaluation provides evidence to suggest Flourish-HE is an effective wellbeing programme that can be delivered to students in Higher Education.